2010
DOI: 10.1136/jech.2009.097709
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between residential proximity to extremely low frequency power transmission lines and adverse birth outcomes

Abstract: Residential proximity to transmission lines is not associated with adverse births outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…In addition, the results from some studies have indicated that exposure to magnetic field may be associated with the increased risk of adverse birth outcomes such as low birth weight [16] and miscarriages [17]. Some studies, however, did not find a statistically significant increased risk of preterm birth and low birth weight in relation to exposure to electromagnetic field during pregnancy [18,19] reproductive outcomes [14]. Pregnant women in Iran sometimes live very close to very high voltage overhead power lines and are exposed to electromagnetic fields [11].…”
Section: Introductionmentioning
confidence: 81%
“…In addition, the results from some studies have indicated that exposure to magnetic field may be associated with the increased risk of adverse birth outcomes such as low birth weight [16] and miscarriages [17]. Some studies, however, did not find a statistically significant increased risk of preterm birth and low birth weight in relation to exposure to electromagnetic field during pregnancy [18,19] reproductive outcomes [14]. Pregnant women in Iran sometimes live very close to very high voltage overhead power lines and are exposed to electromagnetic fields [11].…”
Section: Introductionmentioning
confidence: 81%
“…To compute residential proximity to power lines, the latitudes and longitudes of postal codes (N=89 473) were determined with geocoding software 6. Postal codes typically cover one side of a street block 6.…”
Section: Methodsmentioning
confidence: 99%
“…Postal codes typically cover one side of a street block 6. The straight line distance between postal code centroids and the nearest power line was calculated with MapInfo Professional 8.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cancer, some epidemiological studies have suggested that ELF-MF exposure is associated with an increased risk of other diseases, including neurodegenerative diseases, cardiovascular diseases, and adverse pregnancy outcomes [4–7]. However, other epidemiological studies have indicated a lack of any association [810], and laboratory studies have not provided consistent evidence supporting the epidemiological observations of associated increased disease risk [11, 12]. Generally, the biological effects induced by low-intensity ELF-MFs have not been determined, and the potential underlying mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%